Nuclei‐Specific Amygdala Enlargement Is Linked to Psychiatric Comorbidities in Drug‐Resistant Focal Epilepsy - Hélène Mourre; Julia Makhalova; Lisa Soncin; Elodie Garnier; Hugo Dary; Arnaud Le Troter; Roy A. M. Haast; Benoit Testud; Marie Arthuis; Samuel Medina Villalon; Stanislas Lagarde; Francesca Pizzo; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Amygdala enlargement has been the subject of controversial studies regarding its significance in terms of pathogenicity both in epilepsy and in psychiatric comorbidities such as anxiety, depression, and post‐traumatic stress disorder. However, no causal link has been established in either direction, and the role of distinct amygdala nuclei remains unknown. We investigated volumetric changes of the amygdala and its nine main nuclei and their associations with psychiatric comorbidities in patients with drug‐resistant focal epilepsy. Methods Eighty‐seven adult patients with drug‐resistant focal epilepsy, available 7 T MRI, and completed standardized psychiatric assessments were included. Whole amygdala and nuclei volumes were quantified and compared to healthy controls. Correlations between the amygdala or nuclei volumes and psychiatric scores were analyzed, as well as the prevalence and severity of each comorbidity depending on the presence of enlargement. Results Amygdala enlargement was present in 41% of patients, with bilateral enlargement observed in 30% of these cases, while atrophy was noted in 2%. Bilateral enlargement correlated with higher posttraumatic stress disorder and depression scores. Central nucleus enlargement was associated with a greater prevalence of depression and more severe anxiety. Bilateral enlargement of distinct nuclei in the basolateral group was linked to more severe depression or posttraumatic stress disorder. Interpretation These findings suggest that bilateral amygdala enlargement, particularly in specific nuclei, may serve as a morphological marker of psychiatric comorbidities in epilepsy. Further research is needed to explore the specific roles of amygdala nuclei in psycho‐epileptogenesis.